Recommendation system for billing offers in retail business CRM of a lending agency - Alexander A. Kovalev; A.V. Mezhuev (Цифровые модели и решения)
In the modern world of financial services and banking, lending agencies face increasing competition and the need to constantly improve the quality of customer service. CRM systems allow companies to collect, store and analyze customer data to help better understand their needs and preferences. However, as the customer base and the amount of data grow, it becomes more difficult to analyze information manually and make decisions on personalized offers for each customer. This is where recommender systems come to the rescue. This article discusses the use of various recommender systems for submitting sales offers in CRM, since there is no universal approach to solve this problem. The current state of research in recommender systems and their application in the financial domain is analyzed. The architecture and algorithms for developing of this system are proposed, taking into account the specifics of banking data and business processes. The effectiveness of the recommender system in real bank operating conditions is evaluated.